Challenges and Prospects of Marketing Student-made Computer Software - ABAH, Joshua Abah; Imoter, Iorember (Journal of Internet and Software Engineering, 2025)
This research examines the challenges and prospects of marketing student-made software, focusing on key factors such as market recognition, infrastructural barriers, financial constraints, and competition from foreign brands. The study aims to provide an in-depth analysis of the current state of the Nigerian software industry, identifying obstacles that hinder its growth and opportunities that can be leveraged for expansion and development. A descriptive research design was employed to gather primary data from stakeholders, including student software developers, IT professionals, business owners, and end-users. The instrument for data collection is a validated researcher-developed questionnaire titled “Challenges and Prospects of Marketing Student-made Software”. The quantitative data from the questionnaires was analyzed using descriptive statistics of percentages, means, and standard deviations.  The study's findings reveal that Nigerian student-made software faces significant market visibility challenges, primarily due to inadequate marketing strategies and consumer preference for foreign software solutions. Moreover, infrastructural deficiencies, particularly unreliable electricity and poor internet connectivity, significantly impact software adoption and development. Financial constraints, including limited access to venture capital and high-interest rates on loans, present another significant challenge. Many Nigerian software companies struggle to secure funding, limiting their ability to scale and compete effectively. Furthermore, competition from well-established foreign brands has made it difficult for local software firms to gain a foothold in both domestic and international markets. However, the study identifies promising opportunities in fintech, e-commerce, and education technology, where Nigerian developers can leverage localized solutions to meet specific market demands. The study concludes that overcoming these challenges requires a multi-faceted approach involving government support, improved infrastructure, increased funding opportunities, and strategic marketing efforts. Recommendations include the implementation of favourable government policies, investment in technology infrastructure, financial incentives for student software developers, and enhanced collaboration between industry stakeholders and academic institutions. The outcomes of this study expressed the hope that by addressing these barriers and harnessing available opportunities, Nigeria’s software industry can experience significant growth and contribute to the nation’s economic advancement. The study provides valuable insights for policymakers, business leaders, and technology innovators looking to foster a thriving software ecosystem in Nigeria.